З ІСТОРІЇ МІСТЕЧКА ВЕЛИКИЙ ТОКМАК (Zaporizhzhia Historical Review, 2021)
In the article the process of status changing of the settlement Bolshoy Tokmak of Tavrical province towards small town (mestechko) is considered, and the role of the Jewish population in these events in the second half of the 19th century